2021
DOI: 10.51847/6wcgdxhwpu
|View full text |Cite
|
Sign up to set email alerts
|

Role of Parents in Motivating Children for Orthodontic Treatment; A Cross-Sectional Study Done in Riyadh

Abstract: This cross-sectional study aimed to assess the role of parents in motivating children for orthodontic treatment. The study subjects comprised parents and children who volunteered from different socio-economic classes and had different education levels. The role of parents in motivating children for orthodontic treatment was measured using a 15 items questionnaire. After ensuring the reliability of the questionnaire, differences across gender, education, and family income were seen using a statistical measure C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Human trials have revealed that dietary supplementation with magnolol affects only 1/22 of patients with symptoms including heartburn, thyroid malfunction, or shaking hands. Still, the link between these symptoms and treatment has yet to be established [24][25][26][27]. Carvacrol has been approved for food use by the Food and Drug Administration.…”
Section: Introductionmentioning
confidence: 99%
“…Human trials have revealed that dietary supplementation with magnolol affects only 1/22 of patients with symptoms including heartburn, thyroid malfunction, or shaking hands. Still, the link between these symptoms and treatment has yet to be established [24][25][26][27]. Carvacrol has been approved for food use by the Food and Drug Administration.…”
Section: Introductionmentioning
confidence: 99%